Case Report: Evaluation of COL4A5 non-canonical splicing variants in two families - Koh, Chee Teck; Lim, Tina Si Ting; Loh, Alwin Hwai Liang; Ng, Yan Fei; Kwek, Jia Liang; Lau, Perry Yew Weng; Chin, Hui-lin; Ng, Jun Li; Than, Mya; Mok, Irene Yanjia; Lim, Cynthia Ciwei; Chong, Kay Yuan; et al. (Frontiers in Medicine, 2025)
IntroductionAlport syndrome is one of the most prevalent monogenic kidney diseases, resulting from the defects in COL4A3, COL4A4, and/or COL4A5 genes. Interpretation of non-canonical splicing variants can be challenging. This study aimed to resolve two variants at non-canonical splice sites in the COL4A5 gene using multiple modalities.MethodsExome sequencing was performed on two families suspected of having Alport syndrome. Intronic splice site variants in COL4A5, which have been reported in the literature, were identified: c.1032 + 4A > G in one family and a four-nucleotide deletion, c.1032 + 3_1032 + 6delAAGT, in the other. To clarify the pathogenicity of these variants, several analyses were performed: familial co-segregation analyses in relation to comprehensive phenotyping of family members, immunofluorescence analysis of kidney biopsy specimens to evaluate collagen IV α5 staining patterns, and minigene splicing assay to assess the impact on pre-messenger RNA (mRNA) splicing.ResultsThe family studies demonstrated co-segregation of the variants among members with characteristic phenotypic features. The immunofluorescence analysis of the kidney biopsy samples displayed aberrant collagen IV α5 staining patterns. The minigene splicing assay revealed that both variants caused exon 18 skipping in the COL4A5 gene, resulting in truncated transcripts.ConclusionThe study demonstrated a multi-faceted approach to improve the diagnostic accuracy and clinical utility of genetic testing for Alport syndrome.